New techniques of intra-satellite communication and ranging/time synchronization for autonomous formation flyer - LI Xue; ZHANG Qi-shan; XU Yong; WANG Ce (Tongxin xuebao)
The technique of intra-satellite communication networking and asynchronous ranging for autonomous forma-tion flyer（AFF） were researched. The hybird FDMA/CDMA mode was developed for AFF communication networking,and precisely ranging ＆ time synchronization was performed by bidirection Asynchronous transfer frame of CCSDS proximity-1 protocol via intra-satallite microwave link in AFF. The principle of two-way noncoherent ranging mode about direct sequence spread spectrum（DSSS） was presented for intersatallite ranging/time synchronization in AFF FDMA/ CDMA networks,concerned equations were constructed and two iteration compupting algorithms were derived. Then,the ground experimenting systems for studying and testing the performance of intra-satallite communication and two-way noncoherent ranging/time synchronization were presented with many experiment results and analyzing. Ex-periment results show that the satisfied performance is obtained.